Exploring Strategies and Challenges Faced by Novice Teachers in Preparing Students for the Minimum Competency Assessment: a Case Study in Indonesia - Suryani, Rita; Pratiwi, Naning (SEAMEO Regional Centre for QITEP in Mathematics, 2024)
Indonesia has reformed its assessment system from a national examination to a minimum competency assessment (AKM), focusing on literacy and numeracy skills. Such a change might significantly affect how teachers teach, especially novice ones. Hence, this study explores the strategies and challenges of six novice mathematics teachers as they prepare their students for the AKM. In this qualitative case study research, participants who were mathematics teachers, with no more than five years of teaching experience, were recruited through purposive sampling to engage in semi-structured interviews. Moreover, six lesson plans, before and after the announcement of the AKM, were collected to get a picture of how they modified their teaching and planning. The data from interviews and lesson plans were analysed through the thematic-analysis method to get two main findings. Initially, the novice teachers undertook proactive measures to prepare their students for the assessment. They employed a responsive teaching approach, adapted lesson plans, participated in professional development programmes, and conducted AKM courses. Nevertheless, their efforts were hindered by their limited teaching experience and inadequate professional development opportunities in numeracy instruction. These findings serve to enlighten educators, school administrators, and other stakeholders about the perceptions and challenges faced by teachers in light of assessment reform